2019
DOI: 10.11646/zootaxa.4706.3.10
|View full text |Cite
|
Sign up to set email alerts
|

First report of Gieysztoria falx Brusa, Damborenea & Noreña, 2003 (Platyhelminthes: Rhabdocoela) in southern Brazil

Abstract: Within Dalyelliidae Graff, 1905, Gieysztoria Ruebush & Hayes, 1939 is the most widely distributed and speciose genus, members of which live in marine, brackish, or freshwater habitats (Van Steenkiste et al., 2012). Gieysztoria is composed by ~97 free-living species (Tyler et al. 2016), and species identification is mainly made on the male copulatory system, which has an armed penis (stylet) with different configurations of spines (Noreña et al., 2016). The stylet configuration of Gieysztoria species is tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Regarding less dominant species, such as microturbellarians, most of them are widely distributed and well-known. We found a few species that are representatives of the Neotropical region (e.g., Gieysztoria falx, G. duopunctata, G. evelinae, G. hermes, G. hymanae, Stenostomum paraguayense, and Bothromesostoma evelinae) as other authors reported earlier (Martín 1908, Marcus 1946, Brusa et al 2003, Reyes et al 2019, Reyes et al 2021. The abundance of microturbellarians in the neotropics depends mainly on the life cycle and flooding (Noreña-Janssen 1995).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Regarding less dominant species, such as microturbellarians, most of them are widely distributed and well-known. We found a few species that are representatives of the Neotropical region (e.g., Gieysztoria falx, G. duopunctata, G. evelinae, G. hermes, G. hymanae, Stenostomum paraguayense, and Bothromesostoma evelinae) as other authors reported earlier (Martín 1908, Marcus 1946, Brusa et al 2003, Reyes et al 2019, Reyes et al 2021. The abundance of microturbellarians in the neotropics depends mainly on the life cycle and flooding (Noreña-Janssen 1995).…”
Section: Discussionsupporting
confidence: 85%
“…Species rarefaction curves for each site were built based on the accumulation of individuals (abundance) (Colwell & Elsensohn 2014), so that biases in comparisons due to differences in the abundance of some turbellarians species were corrected (Gotelli & Colwell 2001). Because the ESEC Taim has few previously published records of turbellarian species (Reyes et al 2019, Reyes et al 2021, we tested the performance of five non-parametric richness estimators, based on abundance (Chao 1) and incidence (Chao 2, Jacknife 1, Jacknife 2, and Bootstrap), to determine the completeness of the species inventory. Hence, richness estimators were used to understand the alpha diversity in each sampling site and considering the ESEC Taim as a whole (14 samples).…”
Section: Data Analysesmentioning
confidence: 99%